Law Economic Development: A Study Of Economic Protection And Recovery Policies In The Pandemic Covid-19 - Irawansah, Didik; Ridwan; Kuswardani (Universitas Muhammadiyah Surakarta, 2022)
This study describes the role of law in the development and recovery of Indonesia's national economy in the era of the Covid-19 pandemic and describes various policies for protection and economic recovery in the MSME sector during the Covid-19 pandemic and its implications. Method, normative juridical law research which bases its analysis on legal documents that are closely related to the problem under study. Analyzed by analytical descriptive, qualitative conclusion. Research Results: The Indonesian Government's policies have been responsive enough to overcome the pandemic, this is indicated by the various policies issued to regulate sectors affected by the co-19 pandemic, especially in the MSME sector. But it is felt that at the implementation stage it has not been able to target to the lowest point, this condition is characterized by complicated and procedural regulatory constraints, too rigid budgeting and administration barriers, weak coordination and supervision and overlapping authority in managing and providing assistance to beneficiaries. Novelty: Belum ada penelitian yang mempelajari Ragam Kebijakan PEN dalam Pemulihan Ekonomi di Indonesia Pasca Pandemic Covid 19